Anaphylactic reaction after intravenous injection of ketorolac for colicky pain: a case report and literature review - Karki, Susmin; Shrestha, Gentle Sunder; Yadav, Sushil Kumar; Shah, Ravi; Agrawal, Saurav; Parajuli, Asmita (Journal of Advances in Internal Medicine, 2023)
A 26-year male came to the emergency department complaining of left flank pain. On examination, the patient was afebrile with stable vitals. With clinical features, lab investigations, and ultrasonographic findings, a diagnosis of left hydroureteronephrosis was made. He was managed with intravenous ketorolac 30mg, after which he developed an anaphylactic reaction, and the patient was contained in the red area of the emergency. Anaphylactic reaction to intravenous ketorolac is rarely reported. Ketorolac is one of the common drugs used in pain management in acute care settings; health professionals should be aware of the possible complication in the form of an anaphylactic reaction, which is rare yet potentially fatal.